Writing the Americas in enlightenment Spain - Neal, Thomas Cassidy (Bucknell University Press, 2017)
How did literary discourse about empire contribute to discussions about the implications of modernity and progress in eighteenth-century Spain? Writing the Americas seeks to answer this question by examining how novels, plays and short stories imagined and contested core notions about enlightened knowledge. Expanding upon recent transatlantic and postcolonial approaches to Spain's Enlightenment that have focused mostly on historiographical and scientific texts, this book disputes the long-standing perception of the Spanish Enlightenment as an
Keywords: Spanish literature; Enlightenment; Spanish American literature